2002
DOI: 10.1097/00042737-200208000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole 40 mg and 20 mg is efficacious in the long-term management of patients with endoscopy-negative gastro-oesophageal reflux disease: a placebo-controlled trial of on-demand therapy for 6 months

Abstract: Esomeprazole 20 mg was superior to placebo for on-demand treatment of GORD; a higher dose did not confer additional clinical benefit. Over 90% of patients were willing to continue on-demand treatment with esomeprazole 20 mg over a 6-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
128
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 14 publications
8
128
1
1
Order By: Relevance
“…On the other hand, in the study of Scholten et al (16), no difference was found between patients using pantoprazole at the standard dose and at the maintenance dose at the end of the 6 th month in terms of the mean symptom load (2.7 vs. 2.9, p>0.05). Similarly, at the end of the 6 th month, there was no difference between patients receiving esomeprazole at the standard dose and at the maintenance dose with regard to symptomatic remission rates (17). On the other hand, in a study in which Caos et al (18) compared the usage of rabeprazole 20 mg/day and rabeprazole 10 mg/day, endoscopic recurrence rates were found to be higher in the rabeprazole 10 mg/day group at the end of 5 years of medication therapy (11% vs. 23%, p<0.05).…”
Section: Recommendationsmentioning
confidence: 87%
“…On the other hand, in the study of Scholten et al (16), no difference was found between patients using pantoprazole at the standard dose and at the maintenance dose at the end of the 6 th month in terms of the mean symptom load (2.7 vs. 2.9, p>0.05). Similarly, at the end of the 6 th month, there was no difference between patients receiving esomeprazole at the standard dose and at the maintenance dose with regard to symptomatic remission rates (17). On the other hand, in a study in which Caos et al (18) compared the usage of rabeprazole 20 mg/day and rabeprazole 10 mg/day, endoscopic recurrence rates were found to be higher in the rabeprazole 10 mg/day group at the end of 5 years of medication therapy (11% vs. 23%, p<0.05).…”
Section: Recommendationsmentioning
confidence: 87%
“…On-demand treatment may be more acceptable to patients than the requirement to take medication every day on a long-term basis [10] . In placebo-controlled trials, esomeprazole 20 mg on demand has been shown to be effective and well tolerated in the maintenance of symptom control in patients with NERD [18,19] . In the present study, more patients discontinued from the 8-wk than the 2-wk treatment arm, which may have been the result of the different drug exposures in the treatment period and the difference in assigning maintenance/on-demand treatment in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Inhibition of STAT3 with several agents has also been shown to lead to growth inhibition and enhanced chemo-sensitivity in HCC cells, supporting the role of STAT3 in HCC development. [5][6][7] In conclusion, based on the above observations, it is reasonable to suggest a potential link between obesity and HCC via activation of STAT3.…”
mentioning
confidence: 89%
“…The study is instructive in three ways: first, although similar studies have been performed in Europe, [2][3][4][5][6] there is evidence of differences to responses to PPI [7][8][9] and indeed in the pathogenesis of GERD in different ethnic groups. 10 Therefore, it is essential to confirm that the findings from European studies are indeed applicable to the US population at large, which is ethnically different in make-up to the European population.…”
Section: Acknowledgementmentioning
confidence: 99%